Alih Kode dan Campur Kode pada Film Perempuan Berkalung Sorban Serta Implikasinya Terhadap Pembelajaran Bahasa Indonesia Di SMK Negeri 18 Jakarta - Hayati, Wardah (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This study was aimed to gain data and comprehention of code switching and code mixing, moreover, it investigated why code switching amel code mixing accurared on the movice of perempuan berkalung sorban on the other hand, practicing in indonesian language learning implie that leterature appreciation is not simply abuot intrinsic extrinsiv element. The study was qualitative applying qualitative descriptive. The study analysed the mouve in order to comprehend why code switching and code mixing accured on the movie. The Results of research on code switching and code-mixing the movie  perempuan  Berkalung discovered in dialogues, moreover, the reason why code switching and code mixing occured was also found in the movie. The writer concluded that code switchingandcodemixing existed intheformofdialogues such as phrase and sentence in short, code switching and code mixing can be implemented in literartur study at school espeaully vocational school